Knowledge of community pharmacists about the risks of medication use during pregnancy in central region of Saudi Arabia - Ziyad Alrabiah; Mohamed N. Al-Arifi; Sultan M. Alghadeer; Syed Wajid; Ali AlQahtani; Naif Almotari; AbdAllh AlHwerani; Salmeen D. Babelghaith (Saudi Pharmaceutical Journal)
Background: Community pharmacists (CPs) are the most accessible health care provider to the public, and they have huge duties to improve medication use especially among the pregnant women in their community. The objective of this study was to evaluate knowledge of CPs about the medication safety during pregnancy. Methods: A prospective cross-sectional survey was carried out over practicing community pharmacists in a capital of Saudi Arabia (SA). Pharmacists were asked about the safety of each medicine during pregnancy. It involved both prescription-only medications (POM) and over-the-counter (OTC) medications. Both descriptive and analytic statistics were utilized. For descriptive analysis, results were expressed as numbers, percentages and mean (±SD and 95% CI). Results: The response rate was (71.1%). Most of the respondents (69.6%) believed that alprazolam is not safe while 22% of respondents believed that it is used on basis of risk-benefit assessment. Also, most of CPs (65.2%) said that amoxicillin is safe, but a very few of CPs (11.7%) knew that tetracycline should be used only if potential benefits may outweigh the risk. Among non-prescribed analgesics, majority of CPs (92.6%) knew that acetaminophen is safe. About dietary supplements, 48.4% of CPs reported that Vitamin A supplements are not safe. There was significant difference observed between age groups of CPs in scores of knowledge test (P = 0.001). Conclusion: Community Pharmacists are the most accessible health care providers who can help pregnant women with their medications use there are still gaps in knowledge where educational interventions are needed.